Montanist Regional Bishops: New Evidence from Ancient Inscriptions - Tabbernee, William (Journal of early Christian studies, 1993)
The unique Montanist office of koinōnos may have been introduced by Montanus himself as a means of ensuring that the essential nature of "the New Prophecy" would survive the inevitable institutionalization of Montanism. Even if koinōnoi were a feature only of later Montanism, a plausible connection can be made between them and the earliest companions of Montanus. By c. 380, but probably much earlier, koinōnoi were regional bishops who made sure that the Montanist tradition was handed on faithfully and that "the New Prophecy" continued to be taught and practiced in the region for which they were responsible.